Mistress of All Evil : A TALE OF THE DARK FAIRY - Valentino, Serena (Sywell, United Kingdom : Autumn Publishing, 2018)
"The tale is told as if it's happening once upon a dream: the lovely maiden meets her handsome prince in the woods. The story has been told many times and in many ways. But always the maiden finds out that she is a princess-a princess who has been cursed by a dark fairy to prick her finger on a spindle and fall into an eternal sleep. Though her three good fairies try to protect her, the princess succumbs to the curse. But the power of good endures, as her true love defeats the fire-breathing dragon and awakens the princess with true love's first kiss. The two live happily ever after. And yet this is only half the story. So what of the dark fairy, Maleficent? Why does she curse the innocent princess? What led to her becoming so filled with malice, anger, and hatred? Many tales have tried to explain her motives. Here is one account, pulled down from the many passed down through the ages. It is a tale of love and betrayal, of magic and reveries. It is a tale of the Mistress of All Evil. "--
"Adapted in part from Disney's Sleeping Beauty"--Title page verso
Keywords: Children stories, English; English fiction; Good and evil -- Juvenile fiction; Sleeping beauty (Tale) -- Juvenile fiction